Barbiturate-refractory epilepsy: safe schedule for therapeutic substitution - Ana Maria Gorz; Carlos E. S. Silvado; Paulo Rogério M. Bittencourt (Arquivos de Neuro-Psiquiatria)
Barbiturates are considered first line antiepileptic drugs in third world countries due to traditional and economic reasons. This prospective uncontrolled study of 52 patients aged 15 to 64 years (mean 24) demonstrates that patients who become refractory to barbiturates are mainly those with partial seizures with or without generalization or with a focal EEG abnormality (71%). Seizures tend to become refractory approximately 6 years after barbiturates were started. Progressive barbiturate withdrawal over a period of two to 8 months (mean 5) with institution of treatment with carbamazepine, phenytoin or sodium valproate allowed complete barbiturate withdrawal in 42 of the 52 patients (81%). Furthermore monthly seizure frequency in those in whom barbiturates were withdrawn decreased from 7.1 to 1.7 per patient. An improvement in mental status was observed but not measured. These results show that barbiturates should not be first-choice drugs in patients who have a chronic disease such as epilepsy, and indicate a schedule for barbiturate withdrawal Which is safe and independent of hospitalization or monitoring of antiepileptic drug serum concentrations.